Degradasi Jaringan TD-LTE 2.300 – 2.400 MHz Akibat Interferens Alur-Waktu Silang - Muhammad Suryanegara; Reyfista Pangestu (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
Indonesia has set the frequency band 2,300-2,400 MHz (3GPP band 40) as one of the frequency allocations for the TD-LTE mobile network. Consequently, the implementation of TD-LTE should pay attention to the phenomenon of Crossed Timeslot Interference (CTI) which can occur as a result of the operators’ uplink-downlink configurations. A work simulating the impact of CTI interference that occurs between two network operators having an adjacent spectrum allocation is developed. Network performance indicator is measured through the value of Bit Error Rate (BER) and throughput value of Physical Downlink Shared Channel (PDSCH). The results show that the CTI has caused a degeneration of BER leading to a reduction of throughput value of PDSCH by 15.29%. This work is expected to be a reference for Indonesian network operators to pay more attention to the phenomenon of CTI which could potentially cause degradation of TD-LTE network performance.